Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure! Let's prove that [tex]\((a + b) + c = a + (b + c)\)[/tex] and identify the name of the property. Given the values [tex]\(a = 5\)[/tex], [tex]\(b = -7\)[/tex], and [tex]\(c = 3\)[/tex]:
1. First, we calculate the left-hand side of the equation: [tex]\((a + b) + c\)[/tex].
- Calculate [tex]\(a + b\)[/tex]:
[tex]\[ 5 + (-7) = -2 \][/tex]
- Now, add [tex]\(c\)[/tex] to the result:
[tex]\[ -2 + 3 = 1 \][/tex]
Hence, the left-hand side [tex]\((a + b) + c = 1\)[/tex].
2. Next, we calculate the right-hand side of the equation: [tex]\(a + (b + c)\)[/tex].
- Calculate [tex]\(b + c\)[/tex]:
[tex]\[ -7 + 3 = -4 \][/tex]
- Now, add [tex]\(a\)[/tex] to the result:
[tex]\[ 5 + (-4) = 1 \][/tex]
Hence, the right-hand side [tex]\(a + (b + c) = 1\)[/tex].
Since [tex]\((a + b) + c = 1\)[/tex] and [tex]\(a + (b + c) = 1\)[/tex], we have shown that:
[tex]\[ (a + b) + c = a + (b + c) \][/tex]
The property demonstrated here is called the Associative Property of addition. This property states that the way in which numbers are grouped when being added does not change their sum.
1. First, we calculate the left-hand side of the equation: [tex]\((a + b) + c\)[/tex].
- Calculate [tex]\(a + b\)[/tex]:
[tex]\[ 5 + (-7) = -2 \][/tex]
- Now, add [tex]\(c\)[/tex] to the result:
[tex]\[ -2 + 3 = 1 \][/tex]
Hence, the left-hand side [tex]\((a + b) + c = 1\)[/tex].
2. Next, we calculate the right-hand side of the equation: [tex]\(a + (b + c)\)[/tex].
- Calculate [tex]\(b + c\)[/tex]:
[tex]\[ -7 + 3 = -4 \][/tex]
- Now, add [tex]\(a\)[/tex] to the result:
[tex]\[ 5 + (-4) = 1 \][/tex]
Hence, the right-hand side [tex]\(a + (b + c) = 1\)[/tex].
Since [tex]\((a + b) + c = 1\)[/tex] and [tex]\(a + (b + c) = 1\)[/tex], we have shown that:
[tex]\[ (a + b) + c = a + (b + c) \][/tex]
The property demonstrated here is called the Associative Property of addition. This property states that the way in which numbers are grouped when being added does not change their sum.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.